The Role of Plasma Membrane Aquaporins in Regulating the Bundle Sheath-Mesophyll Continuum and Leaf Hydraulics. Issue 3 (29th September 2014) - Sade, Nir; Shatil-Cohen, Arava; Attia, Ziv; Maurel, Christophe; Boursiac, Yann; Kelly, Gilor; Granot, David; Yaaran, Adi; Lerner, Stephen; Moshelion, Menachem
Abstract : Silencing aquaporins of the xylem bundle sheath cells reduces leaf hydraulic conductance and affects the water permeability of adjacent mesophyll cells, suggesting a bundle sheath-mesophyll feed-forward hydraulic control . Abstract: Our understanding of the cellular role of aquaporins (AQP s) in the regulation of whole-plant hydraulics, in general, and extravascular, radial hydraulic conductance in leaves (Kleaf ), in particular, is still fairly limited. We hypothesized that the AQP s of the vascular bundle sheath (BS ) cells regulate Kleaf . To examine this hypothesis, AQP genes were silenced using artificial microRNAs that were expressed constitutively or specifically targeted to the BS . MicroRNA sequences were designed to target all five AQP genes from the PLASMA MEMBRANE-INTRINSIC PROTEIN1 (PIP1) subfamily. Our results show that the constitutively silenced PIP1 (35S promoter) plants had decreased PIP1 transcript and protein levels and decreased mesophyll and BS osmotic water permeability (Pf ), mesophyll conductance of CO2, photosynthesis, Kleaf, transpiration, and shoot biomass. Plants in which the PIP1 subfamily was silenced only in the BS (SCARECROW:microRNA plants) exhibited decreased mesophyll and BS Pf and decreased Kleaf but no decreases in the rest of the parameters listed above, with the net result of increased shoot biomass. We excluded the possibility of SCARECROW promoter activity in the mesophyll. Hence, the fact that SCARECROW:microRNA mesophyll exhibited reduced Pf, but not reduced mesophyll conductance of CO2, suggests that the BS -mesophyll hydraulic continuum acts as a feed-forward control signal. The role of AQP s in the hierarchy of the hydraulic signal pathway controlling leaf water status under normal and limited-water conditions is discussed.